Kemerovo Regional Medical Exercises Dispensary in 1949–1965 - Anton S. Karelin (СибСкрипт, 2023)
The establishment of the Kemerovo Region in 1943 marked the institutionalization of regional physical culture and sports management bodies. Regional sports competitions needed medical support and control. The Kemerovo Regional Medical Exercises Dispensary appeared in 1949 as an important structural component of the system of medical control and medical support of physical culture and sports in the Kemerovo Region. The archives of the Regional Health Department and the Kemerovo Regional Medical Exercises Dispensary made it possible to determine the advantages and shortcomings of the new institution. The author relied on the principles of historicism and objectivity, as well as on the methods of problem chronology and historical system, to describe the role of the Dispensary in the new system of medical support of physical culture and sports in the postwar years. In the mid-1950s, the Kemerovo Region developed an elaborated network of institutions of medical and physical therapy service, and the Dispensary became a core institution that organized its work. The early 1960s saw a steady increase in the number of medical control and physical therapy services. The Dispensary acquired new functions but suffered from poor facilities and staffing until the mid-1960s, which restrained its developmental potential. The state used the positive experience gained during World War II to improve the network of medical and physical therapy institutions. In 1949–1965, the Kemerovo Region introduced a fundamentally new system of medical support for physical culture and sports.